The Line, the Crack, and the Possibility of Architecture: Figure, Ground, Feminist Performance - Solga, Kim (Theatre Research in Canada / Recherches théâtrales au Canada, 2008)
How and where do architecture and performance collide? Theatre studies has been, over the course of the last decade, increasingly interested in the relationship between stage and space; that interest, however, has primarily been figured by marrying theories of human geography with studies of theatrical performance. "The Line, the Crack, and the Possibility of Architecture" asks what it might mean to explore the spaces of performance through the lens of another plastic art—the art of building—and investigates what the discourses of architecture theory, both classical and (post)modern, might have to say to those of us who study the vicissitudes of feminist performance. The article tracks a figure I call the guerrilla actress-architect; she uses her performing body to reshape the plastic spaces of her world and asks us to consider the possibility that feminist performance may, in fact, be a kind of living architectural practice. Résumé Où se croisent l’architecture et la performance? Au cours des dix dernières années, des chercheurs en études théâtrales s’intéressent de plus en plus au rapport entre la scène et l’espace. Or, cet intérêt s’est manifesté principalement par le recours à des théories de la géographie humaine dans le contexte d’études de la représentation théâtrale. Solga se demande ce qui se produit quand on regarde l’espace de la performance à travers la lentille d’un autre art plastique : l’art de la construction. Elle explore ensuite ce qu’aurait à dire la théorie de l’architecture, tant classique que (post)moderne, à ceux d’entre nous qui étudions les vicissitudes de la performance féministe. Solga suit enfin la piste de la comédienne-architecte guérilla, une figure qui sort de son corps de comédienne pour transformer les espaces plastiques de son monde et nous demande d’imaginer que la performance féministe peut en fait constituer un type de pratique architecturale vivante.